Adoption of biotechnology innovations for potential commercialization - Farid, Hadi; Silong, Abu Daud; Ismail, Ismi Arif; Sarkar, Saroje Kumar (IDOSI Publications, 2011)
The idea of New Agriculture in Malaysia emphasizes on extensive commercialization for using the potentials and applying modern biotechnology. This study tends to pinpoint the influencing factors affecting the level of adoption of biotechnology innovations in Malaysia from the academic viewpoint. Biotechnology researchers from Universiti Malaya, Universiti Kebangsaan Malaysia, Universiti Putra Malaysia and Universiti Sains Malaysia were identified as the target population. Data collection was done using a researcher-designed questionnaire. The validity was established through a panel of experts and a pilot test. The reliability was measured using Cronbach’s alpha internal consistency test. Multiple linear regressions were conducted to identify the model of the relationship among the variables. Results showed that the level of adoption may be recognized by demand and supply issues. Knowledge, acceptance, fund and cooperation were found to influence the level of adoption of biotechnology innovations from the perspective of university researchers. Some policy recommendations are suggested.